ANALISIS TINGKAT KESEJAHTERAAN PELAKU USAHA DI PELABUHAN NUSANTARA KENDARI - Rahmila, Rahmila; Muthalib, Abd. Azis; Asizah, Nur (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
Based on the results of the study, it was found that the welfare level of enterprises (packaged rice sellers, food and beverage sellers, and fruit sellers) at the Kendari Nusantara Port was divided into three criteria, namely high, medium, low. The number of business actors included in the low welfare level is 1 person (3%). Meanwhile, the number of enterprises with a moderate level of welfare is 23 people (66%). The number of business actors belonging to the high welfare level is 11 people (31%). So it can be concluded that the standard of living of business actors in this case, sellers of packaged rice, sellers of food and drinks, and sellers of fruit at the Kendari Archipelago Port are still in the moderate category, or still less prosperous.